The Combined Attenuation Of Rain And Wind Of Parabolic Antenna At KU-Band Frequencies - Sahaq, Khaled Sahal Amer (2011)
In wireless communication systems, especially satellite and terrestrial communications as well as in radar and remote sensing systems the effect of the rain water accumulated on the antenna surfaces (reflector and feed window) during the rain event is considerable especially at higher frequency bands. This effect is known as wet antenna attenuation and it differs in its mechanism from the rain attenuation which is caused by rain on the propagation path. Wet antenna attenuation is one of many other factors that can degrade the system performance at higher frequency-bands such as the Ku-band.